Waste management by application of quality control tools in the manufacturing industry – a case study. (2nd January 2020) - Singh, Jagdeep; Singh, Harwinder; Singh, Deepinder; Kumar, Vinod
Waste management (WM) is a multi-disciplinary activity involving engineering principles, economics, urban and regional planning, management techniques and social sciences, to minimise the different types of wastes in the processes in the manufacturing industry. This study attempts to improve the performance of magnetic particle inspection machines, remove fire hazardous and reduce the use of kerosene oil using application of root cause analysis through quality control tools in manufacturing Industry. With implementation of tools modified action resources are improved which leads to continuous improvement in productivity and product quality in the organisation.